2023
DOI: 10.3390/life13020568
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approaches in the Drug Development and Delivery Systems for Age-Related Macular Degeneration

Abstract: The number of patients with ocular disorders has increased due to contributing factors such as aging populations, environmental changes, smoking, genetic abnormalities, etc. Age-related macular degeneration (AMD) is one of the common ocular disorders which may advance to loss of vision in severe cases. The advanced form of AMD is classified into two types, dry (non-exudative) and wet (exudative) AMD. Although several therapeutic approaches are explored for the management of AMD, no approved therapy can substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 142 publications
0
1
0
Order By: Relevance
“…However, no pre-clinical or clinical trial employing drug-loaded contact lenses has been identified for treating AMD. Delivery via subretinal methods utilizing transconjunctival or transscleral routes faces challenges due to high invasiveness and limited access to a local region [ 61 ]. In contrast to the aforementioned administration methods, intravitreal injection continues to stand as the only competitive method for drug delivery [ 5 ] ( Figure 3 ).…”
Section: Treatments Based On Hydrogels For Amdmentioning
confidence: 99%
“…However, no pre-clinical or clinical trial employing drug-loaded contact lenses has been identified for treating AMD. Delivery via subretinal methods utilizing transconjunctival or transscleral routes faces challenges due to high invasiveness and limited access to a local region [ 61 ]. In contrast to the aforementioned administration methods, intravitreal injection continues to stand as the only competitive method for drug delivery [ 5 ] ( Figure 3 ).…”
Section: Treatments Based On Hydrogels For Amdmentioning
confidence: 99%